Seven centuries of European economic growth and decline - Fouquet, R; Broadberry, S (American Economic Association, 2015)
This paper investigates very long run pre-industrial economic development. New annual GDP per capita data for six European countries over the last seven hundred years paint a clearer picture of the history of European economic development. First, the paper confirms that sustained growth has been a recent phenomenon, but rejects the argument that there was no long run growth in living standards before the Industrial Revolution. Instead, the evidence demonstrates the existence of numerous periods of economic growth before the nineteenth century - unsustained, but raising GDP per capita. It also shows that many of these economies experienced substantial economic decline. Thus, rather than being stagnant, pre-nineteenth century European economies experienced a great deal of change. Finally, it offers some evidence that, from the nineteenth century, these economies increased the likelihood of being in a phase of economic growth and reduced the risk of being in a phase of economic decline.